Effects of dietary spray-dried plasma protein on nutrient digestibility and growth performance in nursery pigs. (30th November 2021) - Kim, Hansol; Lee, Seung Hyung; Kim, Beob Gyun
Abstract: The objectives were to determine the digestible energy and standardized ileal digestibility of amino acids (AA; Exp. 1) and to determine growth performance (Exp. 2) of two sources of dietary spray-dried plasma protein (SDPP) in nursery pigs. In Exp. 1, twelve nursery barrows (9.8 ± 0.9 kg) were assigned to a quadruplicated 3 × 2 Latin square design with three diets and two periods. Each period consisted of 5 d of adaptation, 2 d of fecal sampling, and 2 d of ileal collection. A basal diet was composed of corn, soybean meal, whey, and sucrose as the sole energy and AA sources. Experimental diets were prepared by replacing 15% of the energy and AA sources in the basal diet with SDPP 1 (manufactured in the United States; 78.2% crude protein and 4, 862 kcal gross energy/kg as-is) or SDPP 2 (manufactured in Korea; 74.3% crude protein and 4, 636 kcal gross energy/kg as-is). Spray-dried plasma protein 1 had greater digestible energy ( P < 0.05), but less ( P < 0.05) standardized ileal digestibility of Lys, Met, Trp, and Thr compared with SDPP 2. In Exp. 2, eighty-four nursery pigs (7.9 ± 0.7 kg) were allotted to three dietary treatments in a randomized complete block design with seven replicate pens and four pigs per pen. Three corn–soybean meal–whey–based diets contained fish meal (6% and 3.5% for days 0 to 14 and 14 to 28, respectively), SDPP 1 (4.5% and 2.7%), or SDPP 2 (5.0% and 3.0%) to maintain same energy and nutrient concentrations. During days 0 to 14 and overall period, pigs fed the diets containing SDPP gained more weight ( P < 0.05) than those fed the fish meal diet with no difference between two SDPP sources. In conclusion, SDPP 1 contains greater digestible energy but less AA digestibility compared with SDPP 2. Growth-promoting effects of both SDPP sources in nursery diets have been clearly demonstrated in this work. Lay Summary: Dietary spray-dried plasma protein (SDPP) is widely used in nursery pig diet due to its high nutrient contents and growth-promoting effects. In the present work, two sources of SDPP were evaluated for energy and amino acid (AA) digestibility and growth performance in nursery pigs. The SDPP 1 produced in the United States contained 78.2% crude protein and 4, 862 kcal gross energy/kg and SDPP 2 produced in Korea contained 74.3% crude protein and 4, 636 kcal gross energy/kg. Spray-dried plasma protein 1 had a greater digestible energy concentration, but less AA digestibility compared with SDPP 2. Pigs fed the diets containing SDPP consumed more feed and grew faster than those fed the fish meal diet with no difference between the two sources of SDPP. Taken together, SDPP 1 contains greater digestible energy but less AA digestibility compared with SDPP 2. Growth-promoting effects of two sources of SDPP on nursery pigs are greater than fish meal with no difference between the two sources of SDPP. Abstract : Spray-dried plasma protein produced in the United States contains greater digestible energy but less ileal amino acid digestibility compared with spray-dried plasma protein produced in Korea. Growth-promoting effects of two sources of spray-dried plasma protein on nursery pigs are greater than fish meal with no difference between the two sources of spray-dried plasma protein.